Ultra-Thin Al2O3 Grown by PEALD for Low-Power Molybdenum Disulfide Field-Effect Transistors - Shiwei Sun; Dinghao Ma; Boxi Ye; Guanshun Liu; Nanting Luo; Hao Huang (Journal of Low Power Electronics and Applications)
The lack of ultra-thin, controllable dielectric layers poses challenges for reducing power consumption in 2D FETs. In this study, plasma-enhanced atomic layer deposition was employed to fabricate a highly reliable, ultra-thin aluminum oxide (Al2O3) dielectric layer with a thickness of 4 nm. The Al2O3 film grown on highly conductive silicon substrates demonstrated a maximum breakdown field of 5.98 MV/cm and a leakage current density as low as 2.48 × 10−7 A/cm2 at 1 MV/cm. MoS2 FETs incorporating this Al2O3 gate dielectric exhibited high-performance n-type characteristics at a low operating voltage of 1 V, achieving a subthreshold swing (SS) of 65 mV/dec, a threshold voltage (Vth) of −0.96 V, a high carrier mobility (μ) of 34.85 cm2·V−1·s−1, and an on/off current ratio exceeding 106. These results highlight the potential of Al2O3 in enabling low-power 2D electronic devices for post-Moore applications.